Review on pharmacology activities of Justicia Gendarussa Burm F. - Tanya Jain; Manish Pal Singh; Harsh Bhardwaj; Kashmira J. Gohil (Elsevier, 2024)
Introduction: Traditional remedies made from medicinal plants have been used for human treatment since ancient times. Justicia gendarussa is a medicinal plant belonging to the Acanthaceae family. Its use in traditional medicine for treating various ailments is supported by its scientifically proven pharmacological actions. The plant exhibits a wide range of pharmacological activities such as antidiabetic, antioxidant, antinociceptive, antimicrobial, anticancer, hepatoprotective, and immunomodulatory activities. Methods: We have collected the data which supported this idea to conduct a comprehensive review by using scientific databases such as Pub Med ®, Science Direct ® and Google Scholar ®. The use of suitable keywords in listed scientific search engine like bioactive molecules of Justicia gendarussa, pharmacological activities of herbal plant, medicinal values of natural herbs etc. An attempt was made to refer to all English-language articles published between1987 and 2023. Result & discussion: Therefore, Justicia gendarussa is a promising medicinal plant with various pharmacological activities, and its phytochemical constituents have demonstrated potential as new drug leads for the treatment of various diseases. However, further studies are needed to fully understand its mechanisms of action, safety, and efficacy before it can be recommended for clinical use. The plant was found to have broad spectrum of activities due to the presence of active constituents like alkaloids, flavonoids, phenolic compounds, steroids, carbohydrate, carotenoids and terpenoids.